Numerical investigation on load transfer mechanism of bonded post-tensioned concrete beam-column substructures against progressive collapse - Qian, Kai; Hu, Hai-Ning; Weng, Yun-Hao; Deng, Xiao-Fang; Huang, Ting (Advances in structural engineering, 2021)
This paper presents the high-fidelity finite-element-based numerical models for modeling the behavior of prestressed concrete (PC) beam-column substructures to resist progressive collapse under column removal scenario. After careful calibration against data, the validated numerical models are further employed to shed light on the influence of bonded post-tensioned tendons (BPT) with a parabolic profile on the load transfer mechanisms of PC frames against progressive collapse. The effects of parameters, including initial effective prestress, profile of tendon and lateral constraint stiffness at the beam ends, are also investigated. The study shows that, due to the presence of prestressed tendons, the mobilization of compressive arch action in the beam at small deflections demands stronger lateral constraints, and the ultimate load resistance of PC beam-column substructures depends on combined catenary action from non-prestressed reinforcement and BPT at large deflections. For a given constraint stiffness, the initial effective prestress of BPT has less significant effect on the overall structural behavior. For prestressed tendon, a straight profile usually employed in structural strengthening can improve the initial structural stiffness and yield strength, but is less effective in enhancing the ultimate resistance against progressive collapse than the parabolic profile.